P31-04 Promoting Ethical Drug Development: Reducing NHP use in Preclinical Safety Evaluations of Biologics - A. Bejanariu; W. Touati; L. Sautier; A. Garrigou; F. Chanut; V. Menet (Toxicology Letters, 2025)

P30-66 EPAA review of regulatory requirements for a second (non-rodent) species in repeated-dose toxicity studies and potential 3Rs opportunities - N. Printemps; M. Aggarwal; M. Anderton; P. Bishop; F. Chanut; K. Clark; M. Corvaro; P. Deford; O. Doehr; J. Fretton; J.-C. Garcin; A. Kampkoetter; et al. (Toxicology Letters, 2025)

Investigating overpressure BLEVE effects on 100 % liquid full vessel - E.M. Laamarti; A.M. Birk; C. Chanut; F. Heymes (Process Safety and Environmental Protection, 2025)

Correlations to estimate the ground loading from small scale propane BLEVE experiments - E.M. Laamarti; A.M. Birk; C. Chanut; F. Heymes (Process Safety and Environmental Protection, 2024)

Convergence in floodplain pond communities indicates different pathways to community assembly - P. C. M. Chanut; F. J. Burdon; T. Datry; C. T. Robinson (Aquatic Sciences, 2023)
Disturbance can strongly influence ecosystems, yet much remains unknown about the relative importance of key processes (selection, drift, and dispersal) in the recovery of ecological communities following disturbance. We combined field surveys with a field experiment to elucidate mechanisms governing the recovery of aquatic macroinvertebrates in habitats of an alluvial floodplain following flood disturbance. We monitored macroinvertebrates in 24 natural parafluvial habitats over 60 days after a major flood, as well as the colonization of 24 newly-built ponds by macroinvertebrates over 45 days in the same floodplain. We examined the sources of environmental variation and their relative effects on aquatic assemblages using a combination of null models and Mantel tests. We also used a joint species distribution model to investigate the importance of primary metacommunity structuring processes during recovery: selection, dispersal, and drift. Contrary to expectations, we found that beta diversity actually decreased among natural habitats over time after the flood or the creation of the ponds, instead of increasing. This result was despite environmental predictors showing contrasting patterns for explaining community variation over time in the natural habitats compared with the experimental ponds. Flood heterogeneity across the floodplain and spatial scale differences between the experimental ponds and the natural habitats seemingly constrained the balance between deterministic and stochastic processes driving the ecological convergence of assemblages over time. While environmental selection was the dominant structuring process in both groups, biotic interactions also had a prominent influence on community assembly. These findings have profound implications towards understanding metacommunity structuring in riverscapes that includes common linkages between disturbance heterogeneity, spatial scale properties, and community composition.

Corrigendum to "NEMO on the shelf: assessment of the Iberia–Biscay–Ireland configuration" published in Ocean Sci., 9, 745–771, 2013 - C. Maraldi; J. Chanut; B. Levier; N. Ayoub; P. De Mey; G. Reffray; F. Lyard; S. Cailleau; M. Drévillon; E. A. Fanjul; M. G. Sotillo; P. Marsaleix (Ocean Science, 2013)

NEMO on the shelf: assessment of the Iberia–Biscay–Ireland configuration - C. Maraldi; J. Chanut; B. Levier; N. Ayoub; P. De Mey; G. Reffray; F. Lyard; S. Cailleau; M. Drévillon; E. A. Fanjul; M. G. Sotillo; P. Marsaleix (Ocean Science, 2013)
This work describes the design and validation of a high-resolution (1/36°) ocean forecasting model over the "Iberian–Biscay–Irish" (IBI) area. The system has been set-up using the NEMO model (Nucleus for European Modelling of the Ocean). New developments have been incorporated in NEMO to make it suitable to open- as well as coastal-ocean modelling. In this paper, we pursue three main objectives: (1) to give an overview of the model configuration used for the simulations; (2) to give a broad-brush account of one particular aspect of this work, namely consistency verification; this type of validation is conducted upstream of the implementation of the system before it is used for production and routinely validated; it is meant to guide model development in identifying gross deficiencies in the modelling of several key physical processes; and (3) to show that such a regional modelling system has potential as a complement to patchy observations (an integrated approach) to give information on non-observed physical quantities and to provide links between observations by identifying broader-scale patterns and processes. We concentrate on the year 2008. We first provide domain-wide consistency verification results in terms of barotropic tides, transports, sea surface temperature and stratification. We then focus on two dynamical subregions: the Celtic shelves and the Bay of Biscay slope and deep regions. The model–data consistency is checked for variables and processes such as tidal currents, tidal fronts, internal tides and residual elevation. We also examine the representation in the model of a seasonal pattern of the Bay of Biscay circulation: the warm extension of the Iberian Poleward Current along the northern Spanish coast (Navidad event) in the winter of 2007–2008.

Arching effect on fish body shape in geometric morphometric studies - A. E. Valentin; X. Penin; J.‐P. Chanut; J.‐M. Sévigny; F. J. Rohlf (Journal of Fish Biology, 2008)
Upward and downward arching of the body was observed during a study on redfishes Sebastes sp. population structure in the north‐west Atlantic Ocean. The present study investigated the potential causes of this arching artefact. The results suggested that it is not related to biological factors (size or species) or to the preservation technique (freezing), but is rather due to slight posture differences between fishes during landmark capture. The consequences of the arching artefact on data analysis are discussed. An approach coupling a PCA‐based model of the arching with Burnaby’s orthogonal projection is proposed for removing the artefact from the data.